Rapid Transit, Transit-Oriented Development, and the Contextual Sensitivity of Land Value Uplift in Toronto - Higgins, Christopher D; Kanaroglou, Pavlos S (Urban Studies, 2017)
Rapid transit projects that increase accessibility should result in a localized land value uplift (LVU) benefit for locations near stations. A rich history of research has tested this hypothesis, generally operationalizing transit accessibility by proxy through distance from a transit station. However, a growing body of research has also demonstrated LVU effects from transit-oriented development (TOD) as individuals sort themselves into locations that best match their preferences and willingness to pay. Considering the interdependence of transportation and land use in the urban system, we argue that these benefits create a spatial bundle of TOD goods around transit stations and hypothesize that households are willing to pay a premium for locations in more transit-oriented station catchment areas. Utilizing latent class analysis, we quantify station area TOD submarkets. Next, interactions between these submarkets and station proximity in spatial hedonic regressions reveal that TOD is capitalized into land values in Toronto, though the maximum amount and spatial impact area of this capitalization differs by TOD context.
Keywords: Transit-oriented Development; Urban Planning; Land-use Planning; Applied Econometrics